Method for preparing vinyl acetate, catalyst for preparing vinyl acetate and preparation method of catalyst
By preparing a catalyst with a site coverage of 0 to 10% on the surface, the problem of low selectivity of vinyl acetate synthesis catalysts in the prior art is solved, and higher selectivity and synthesis efficiency are achieved.
Patent Information
- Application Number
- CN202311292862.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-08
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-10-08
AI Technical Summary
In the prior art, the catalyst selectivity of ethylene acetate is low in ethylene gas phase, which affects the reaction efficiency.
A catalyst is provided with a coverage ratio of 0 to 10% on the surface of the Pd-N3 site. It is prepared by immersing the C3N4 dispersion liquid and calcining the catalyst precursor, and processing in an alkaline compound solution, reducing precious metal ion, impregnation of alkali metal acetate, etc.
It significantly improves the selectivity and space-time yield of the catalyst and improves the synthesis efficiency of vinyl acetate.
Abstract
Description
Technical Field
[0001] The invention relates to a catalyst for preparing vinyl acetate, a preparation method thereof and a method for preparing vinyl acetate. Background Art
[0002] As an important organic monomer, vinyl acetate (VAc) is an important raw material for synthesizing chemical products such as polyvinyl alcohol (PVA), polyvinyl acetate (PVA), ethylene-vinyl acetate copolymer resin (EVA), vinyl acetate-vinyl chloride copolymer (EVC) and polypropylene comonomer. It is widely used in synthetic fibers, leather processing, films, vinylon, adhesives, coatings and other fields. Among them, the ethylene gas phase method is one of the most important methods for producing VA in industry at present, which has the advantages of high energy utilization rate and low environmental harm. Especially in recent years, with the opening of the technical route of biomass to ethanol and further dehydration to ethylene, the synthesis of VAc by ethylene gas phase method has received more attention.
[0003] At present, the industrial synthesis of VAc from ethylene by gas phase method mainly uses palladium-gold / potassium acetate / silicon dioxide as catalyst, and the palladium site on the catalyst surface is the main active site. During the reaction, ethylene, oxygen and acetic acid are used as raw materials, and the gas phase catalytic reaction is used to produce vinyl acetate, water and carbon dioxide as a byproduct. The temperature of the reactor shell side of the reaction can be about 100-180°C, the reaction pressure is about 0.5-1.0MPa, and the gas volume space velocity is about 500-3000hr -1 GB1283737 discloses a method for controlling the loading of catalyst components by treating a porous shell with sodium carbonate or sodium hydroxide.
[0004] CN1107831A discloses a scheme for improving metal aging by introducing barium salts onto the surface of a carrier; CN1226188A discloses a method for preparing a catalyst loaded with a main catalyst noble metal, a co-catalyst metal and an alkali metal or alkaline earth metal compound. Summary of the invention
[0005] The purpose of the present invention is to provide a catalyst for preparing vinyl acetate that can significantly improve catalytic selectivity. In order to achieve the above purpose, the present invention provides a catalyst for preparing vinyl acetate, wherein the coverage of the surface Pd-N3 sites of the catalyst is 0 to 10%.
[0006] The second aspect of the present invention provides a method for preparing the catalyst of the present invention, which method comprises:
[0007] (a) impregnating a carrier source into a C3N4 dispersion and calcining to prepare a catalyst precursor I;
[0008] (b) immersing the catalyst precursor I in a solution containing palladium and group IB metals, and drying to prepare a catalyst precursor II;
[0009] (c) treating the catalyst precursor II with a solution of an alkaline compound and drying to obtain a catalyst precursor III;
[0010] (d) reducing the noble metal ions of catalyst precursor III and drying to obtain catalyst precursor IV;
[0011] (e) Impregnating the catalyst precursor IV with alkali metal acetate and drying.
[0012] A third aspect of the present invention provides a method for preparing vinyl acetate, wherein a raw gas for synthesizing vinyl acetate is subjected to a gas-phase catalytic synthesis reaction in the presence of a catalyst, wherein the catalyst includes the catalyst of the present invention.
[0013] Through the above technical solution, the selectivity of the catalyst and the space-time yield of the catalyst can be effectively improved. DETAILED DESCRIPTION
[0014] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0015] The present invention provides a catalyst for preparing vinyl acetate, wherein the coverage of the surface Pd-N3 sites of the catalyst is 0 to 10%. In the present invention, the end value 0 means infinitely close to 0, indicating that the purpose of the present invention can be achieved if it exists.
[0016] According to a preferred embodiment of the present invention, the coverage of the Pd-N3 sites on the surface of the catalyst is 2% to 10%. The catalyst of the present invention can effectively improve the reaction selectivity.
[0017] The present invention has no special requirements on the composition of the catalyst. For example, any commonly used Pd-containing catalyst composition can be used in the present invention. The following is an exemplary description, but it is not intended to limit the scope of the present invention.
[0018] According to one embodiment of the present invention, the catalyst includes a carrier and Pd, a Group IB metal and an alkali metal acetate supported on the carrier.
[0019] In the present invention, all metals of Group IB can be used in the present invention, which is exemplified below, but the scope of the present invention is not limited thereby.
[0020] According to one embodiment of the present invention, for the present invention, the preferred Group IB metal is Au and / or Cu, preferably Au.
[0021] In the present invention, commonly used alkali metal elements can be used in the present invention. The following exemplary description is not intended to limit the scope of the present invention. According to one embodiment of the present invention, the alkali metal element is selected from one or more of Li, Na, K, Rb, Cs, and Fr, preferably one or more of Na and K; preferably, the alkali metal acetate is potassium acetate; thereby, the selectivity of the catalyst can be improved.
[0022] In the present invention, there is no special requirement for the carrier, and the carrier commonly used in the art can achieve the purpose of the present invention. The following exemplary description is not intended to limit the scope of the present invention. According to one embodiment of the present invention, the carrier is selected from one or more of silicon oxide and aluminum oxide. According to a preferred embodiment of the present invention, preferably, the carrier is selected from spherical silicon dioxide, preferably, the diameter of the spherical silicon dioxide is 2-8 mm, and the specific surface area is 150-200 m 2 / g, pore volume is 0.6-1cm 3 / g. The present invention uses a silica carrier with a diameter of 5 mm and a specific surface area of 175 m 2 / g, pore volume is 0.8cm 3 / g is used as an example to illustrate the advantages of the present invention, but does not limit the scope of the present invention.
[0023] In the present invention, there is no special requirement for the content of each substance, and the content commonly used in the art can be used in the present invention. The following is an exemplary description, but the scope of the present invention is not limited thereby.
[0024] According to one embodiment of the present invention, the content of Pd is 1 to 12 g / L, for example, 2.1 g / L, 2.2 g / L, 2.3 g / L, 2.4 g / L, 2.5 g / L, 2.6 g / L, 2.7 g / L, 2.8 g / L, 2.9 g / L, 3 g / L, in terms of element. This can improve the selectivity of the catalyst.
[0025] According to one embodiment of the present invention, the content of Group IB metal is 0.1 to 10 g / L, such as 0.4 g / L, 0.5 g / L, 0.6 g / L, 0.7 g / L, or 0.8 g / L, in terms of element. This can improve the selectivity of the catalyst.
[0026] According to one embodiment of the present invention, the content of alkali metal acetate is 10-100 g / L, preferably 20-40 g / L, for example 20 g / L, 30 g / L, 40 g / L, thereby improving the selectivity of the catalyst.
[0027] In the present invention, the composition of each substance in the catalyst is calculated based on the input materials.
[0028] In the present invention, the Group IB metal in the catalyst mainly exists in the form of a single substance.
[0029] In the present invention, Pd mainly exists in the form of a single substance.
[0030] The catalysts having the above-mentioned characteristics of the present invention can achieve the purpose of the present invention, and there is no special requirement for their preparation methods. According to the present invention, a preparation method of the catalyst for synthesizing vinyl acetate is provided, which comprises:
[0031] (a) impregnating a carrier source into a C3N4 dispersion and calcining to prepare a catalyst precursor I;
[0032] (b) immersing the catalyst precursor I in a solution containing palladium and group IB metals, and drying to prepare a catalyst precursor II;
[0033] (c) treating the catalyst precursor II with a solution of an alkaline compound and drying to obtain a catalyst precursor III;
[0034] (d) reducing the noble metal ions of catalyst precursor III and drying to obtain catalyst precursor IV;
[0035] (e) Impregnating the catalyst precursor IV with alkali metal acetate and drying.
[0036] In the present invention, the optional range of C3N4 concentration in the C3N4 dispersion is relatively wide, which is exemplified below but is not limited to the scope of the present invention. According to one embodiment of the present invention, the content of C3N4 in the C3N4 dispersion is 5-20wt%.
[0037] In the present invention, in step (a), the solid-liquid volume ratio can be selected in a wide range, which is exemplified below but is not limited to the scope of the present invention. The preferred solid-liquid volume ratio is 1:1 to 1.5.
[0038] According to one embodiment of the present invention, in the present invention, the diameter of C3N4 in the C3N4 dispersion is 0.1 to 10 microns, for example, 0.1 micron, 0.5 micron, 1 micron, 2 microns, 3 microns, 4 microns, 5 microns, 6 microns, 7 microns, 8 microns, 9 microns, 10 microns, preferably 2 to 8 microns; C3N4 in the aforementioned diameter range can achieve the purpose of the present invention.
[0039] In the present invention, the solvent of the dispersion liquid can be selected from a wide range, and commonly used solvents can be used in the present invention. For the present invention, it is preferred that the solvent in the dispersion liquid is selected from one or more of deionized water.
[0040] According to a preferred embodiment of the present invention, preferably, the dispersion in step (a) contains an auxiliary agent, and preferably the auxiliary agent is selected from one or more of acetic acid and ammonium acetate: more preferably, the auxiliary agent content is 0.1-10 mmol / L; thereby, the selectivity of the catalyst can be improved.
[0041] According to a preferred embodiment of the present invention, drying is performed before calcination, and the preferred calcination conditions include 300-500°C, for example, 300°C, 350°C, 400°C, 450°C, 500°C; the aforementioned calcination temperatures can all achieve the purpose of the present invention, and 500°C is used as an example in the embodiments of the present invention to illustrate the advantages of the present invention, but the scope of the present invention is not limited thereby.
[0042] In the present invention, there is no special requirement for the calcination time, for example, it can be 1-4 hours (for example, 1 hour, 2 hours, 3 hours, 4 hours), preferably 2-3 hours.
[0043] In the present invention, there is no special requirement for drying conditions, for example, drying is generally carried out at 60-100°C. There is no special requirement for drying time, and the purpose is to dry and remove liquid as much as possible, for example, drying to a solid content of more than 95% by weight, for example, the general drying time is 4-8h.
[0044] In the present invention, there is no special requirement for the carrier source, and any carrier source commonly used in the art can achieve the purpose of the present invention. The carrier source is selected from one or more of silicon dioxide and aluminum oxide; preferably, the carrier source is selected from spherical silicon dioxide, and preferably the diameter of the spherical silicon dioxide is 2-8 mm, and the specific surface area is 150-200 m 2 / g, pore volume is 0.6-1cm 3 / g.
[0045] In the present invention, the operating conditions in step (b) can be selected in a wide range, and there are no special requirements for the present invention. The following is an exemplary description, but it is not limited to the scope of the present invention.
[0046] According to a preferred embodiment of the present invention, the operating conditions in step (b) include:
[0047] The solid-liquid volume ratio is 1:1-1.2. In the solution containing Pd source and IB group metal source, the Pd content is 1-12 g / L, preferably 2-3 g / L, and the IB group metal content is 0.1-10 g / L, preferably 0.4-0.8 g / L.
[0048] In the present invention, the optional range of conditions in step (c) is relatively wide, and the conditions commonly used in the art can be used in the present invention. The following exemplary description does not limit the scope of the present invention. According to one embodiment of the present invention, the conditions in step (c) include: the concentration of the solution of the alkaline compound is 10-30% by weight.
[0049] According to one embodiment of the present invention, the conditions in step (c) include: the volume ratio of the solution of the basic compound to the carrier is 0.05 to 0.5, preferably 0.07 to 0.1.
[0050] In the present invention, the alkaline compound can be selected from a wide range of types. According to a preferred embodiment of the present invention, in step (c), the alkaline compound includes but is not limited to one or more of sodium silicate and sodium hydroxide.
[0051] According to one embodiment of the present invention, the reducing agent used for reduction includes but is not limited to one or more of hydrazine hydrate and sodium citrate. There is no special requirement for the reduction conditions, and the commonly used reduction conditions can be applied to the present invention.
[0052] In the present invention, in steps (a) to (e), the mixture is allowed to stand as required in order to achieve sufficient contact.
[0053] In the present invention, step (a) can be optionally allowed to stand for 12-48 hours as required.
[0054] In the present invention, step (c) can be optionally allowed to stand for 12-48 hours as required.
[0055] In the present invention, step (d) can be optionally allowed to stand for 3-6 hours as required.
[0056] In the present invention, step (e) can be optionally allowed to stand for 3-6 hours as required.
[0057] In the present invention, in steps (a) to (e), water washing is performed before drying as required, and the purpose of water washing is to remove impurity ions such as chloride ions.
[0058] In the present invention, there are no special requirements for the conditions of reduction, optional water washing and drying. Commonly used reduction, water washing and drying conditions can be used in the present invention. According to a preferred embodiment of the present invention, the conditions in step (c) include: reduction time of 1-10 hours; water washing time of 1-20 hours; drying temperature of 60-100°C; drying time of 1-10 hours.
[0059] The present invention provides a method for preparing vinyl acetate. In the presence of a catalyst, raw gas for synthesizing vinyl acetate undergoes a gas-phase catalytic synthesis reaction. The catalyst includes the catalyst of the present invention.
[0060] According to a preferred embodiment of the present invention, the raw gas for synthesizing vinyl acetate includes oxygen, ethylene, nitrogen and acetic acid; preferably, the raw gas composition in a molar ratio is oxygen:ethylene:nitrogen:acetic acid=1:(5-7):(4-8):(1-2).
[0061] According to a preferred embodiment of the present invention, the conditions for the gas phase catalytic synthesis reaction include: the reaction pressure is 0.5 to 0.9 MPa.
[0062] According to a preferred embodiment of the present invention, the conditions for the gas phase catalytic synthesis reaction include: a reaction temperature of 130 to 200°C.
[0063] According to a preferred embodiment of the present invention, the conditions for the gas phase catalytic synthesis reaction include: the raw gas volume space velocity is 1600 to 3000 hr -1 .
[0064] In the present invention, unless otherwise specified, the operation is carried out at room temperature.
[0065] In the present invention, unless otherwise specified, the solvent of the solution is water.
[0066] The present invention will be described in detail below by way of examples. In the following examples,
[0067] The calculation method of catalyst space time yield (STY) and selectivity (SEL) is:
[0068] Assume: A is the amount of ethylene reacted in one day (kmol / d), B is the amount of oxygen reacted in one day, and X is the amount of ethylene consumed by the main reaction in one day.
[0069] X=(3A-B) / 2.5
[0070] STY = 86X / catalyst amount (m 3 )×1000
[0071] SEL=X / A×100%.
[0072] Test method for Pd-N3 site:
[0073] The XPS spectrum can be used for testing, focusing on the peak position of N atoms. The N atoms in the Pd-N3 binding mode will peak at 398-399eV. The proportion of the peak area is the content of the Pd-N3 site.
[0074] Example 1
[0075] 1. Catalyst preparation
[0076] (a) The carrier (silicon dioxide carrier, diameter 5mm, specific surface area 175m 2 / g, pore volume is 0.8cm 3 / g) was immersed in a C3N4 aqueous dispersion (wherein the concentration of C3N4 was 5wt% and the diameter of C3N4 was 5 μm), allowed to stand for 24 hours, with a solid-liquid volume ratio of 1:1.5, dried at 80°C for 6 hours, and calcined at 500°C for 2 hours to prepare a catalyst precursor I;
[0077] (b) 1100 ml of catalyst precursor I was immersed in a mixed aqueous solution of chloropalladic acid and chloroauric acid, with a solid-liquid volume ratio of 1:1.2, wherein the palladium content in the solution was 2.75 g / L and the gold content was 0.625 g / L, and then dried at 80° C. for 8 hours to prepare catalyst precursor II;
[0078] (c) adding 100 ml of sodium silicate aqueous solution (27.5 g of Na2SiO3·9H2O is prepared into 100 ml of aqueous solution), mixing well and letting stand for 24 hours, and then drying at 80° C. for 8 hours to obtain catalyst precursor III;
[0079] (d) adding 60 g of 85% wt hydrazine hydrate for reduction, standing for 4 hours, then washing with deionized water, and drying at 100° C. for 6 hours to obtain catalyst precursor IV;
[0080] (e) The catalyst precursor IV was impregnated with an aqueous solution of potassium acetate and dried at 80° C. for 2 h to obtain a finished catalyst, wherein the potassium acetate content in the catalyst was 30 g / L.
[0081] 2. Catalyst evaluation
[0082] The fixed bed reactor was used for evaluation, and the specific conditions were:
[0083] Catalyst filling volume: 40ml;
[0084] The composition of the reaction raw materials (by molar ratio): oxygen: ethylene: nitrogen: acetic acid = 1: 6.8: 7.5: 1.8;
[0085] Reaction raw material feed volume space velocity: 1950hr -1 ;
[0086] Reaction pressure: 0.7MPa;
[0087] Reaction temperature: 134°C;
[0088] Reaction time: 100hr;
[0089] The content of each component in the reaction product was analyzed by gas chromatography, and then the space-time yield and ethylene selectivity of the catalyst were calculated.
[0090] For the convenience of comparison, the experimental results are listed in Table 1.
[0091] Example 2
[0092] 1. Catalyst preparation
[0093] (a) The carrier (silicon dioxide carrier, diameter 5mm, specific surface area 175m 2 / g, pore volume is 0.8cm 3 / g) was immersed in a C3N4 aqueous dispersion (wherein the concentration of C3N4 was 11%wt and the diameter of C3N4 was 2 μm), allowed to stand for 24 hours, with a solid-liquid volume ratio of 1:1.5, dried at 80°C for 6 hours, and calcined at 500°C for 2 hours to prepare a catalyst precursor I;
[0094] (b) 1100 ml of catalyst precursor I was immersed in a mixed aqueous solution of chloropalladic acid and chloroauric acid, with a solid-liquid volume ratio of 1:1.2, wherein the palladium content in the solution was 2.75 g / L and the gold content was 0.625 g / L, and then dried at 80° C. for 8 hours to prepare catalyst precursor II;
[0095] (c) adding 100 ml of sodium silicate aqueous solution (27.5 g of Na2SiO3·9H2O is prepared into 100 ml of aqueous solution), mixing well and letting stand for 24 hours, and then drying at 80° C. for 8 hours to obtain catalyst precursor III;
[0096] (d) adding 60 g of 85% wt hydrazine hydrate for reduction, standing for 4 hours, then washing with deionized water, and drying at 100° C. for 6 hours to obtain catalyst precursor IV;
[0097] (e) The catalyst precursor IV was impregnated with an aqueous solution of potassium acetate and dried at 80° C. for 2 h to obtain a finished catalyst, wherein the potassium acetate content in the catalyst was 30 g / L.
[0098] 2. Catalyst evaluation
[0099] The catalyst evaluation method was the same as in Example 1.
[0100] For the convenience of comparison, the experimental results are listed in Table 1.
[0101] Example 3
[0102] 1. Catalyst preparation
[0103] (a) The carrier (silicon dioxide carrier, diameter 5mm, specific surface area 175m 2 / g, pore volume is 0.8cm 3 / g) was immersed in a C3N4 aqueous dispersion (wherein the concentration of C3N4 was 20%wt and the diameter of C3N4 was 8 μm), allowed to stand for 24 hours, with a solid-liquid volume ratio of 1:1.5, dried at 80°C for 6 hours, and calcined at 500°C for 2 hours to prepare a catalyst precursor I;
[0104] (b) 1100 ml of catalyst precursor I was immersed in a mixed aqueous solution of chloropalladic acid and chloroauric acid, with a solid-liquid volume ratio of 1:1.2, wherein the palladium content in the solution was 2.75 g / L and the gold content was 0.625 g / L, and then dried at 80° C. for 8 hours to prepare catalyst precursor II;
[0105] (c) adding 100 ml of sodium silicate aqueous solution (27.5 g of Na2SiO3·9H2O is prepared into 100 ml of aqueous solution), mixing well and letting stand for 24 hours, and then drying at 80° C. for 8 hours to obtain catalyst precursor III;
[0106] (d) adding 60 g of 85% wt hydrazine hydrate for reduction, standing for 4 hours, then washing with deionized water, and drying at 100° C. for 6 hours to obtain catalyst precursor IV;
[0107] (e) The catalyst precursor IV was impregnated with an aqueous solution of potassium acetate and dried at 80° C. for 2 h to obtain a finished catalyst, wherein the potassium acetate content in the catalyst was 30 g / L.
[0108] 2. Catalyst evaluation
[0109] The catalyst evaluation method was the same as in Example 1.
[0110] For the convenience of comparison, the experimental results are listed in Table 1.
[0111] Example 4
[0112] The method of Example 2 was followed, except that acetic acid was added to the dispersion in an amount of 0.1 mmol / L.
[0113] Example 5
[0114] The method of Example 2 was followed, except that acetic acid was added to the dispersion in an amount of 8.5 mmol / L.
[0115] Example 6
[0116] The method of Example 2 was followed, except that ammonium acetate was added to the dispersion in an amount of 10 mmol / L.
[0117] Comparative Example 1
[0118] 1. Catalyst preparation
[0119] (a) The carrier (silicon dioxide carrier, diameter 5mm, specific surface area 175m 2 / g, pore volume is 0.8cm 3 / g) was immersed in a C3N4 aqueous dispersion (wherein the concentration of C3N4 was 25wt%), allowed to stand for 24 hours, with a solid-liquid volume ratio of 1:1.5, dried at 80°C for 6 hours, and calcined at 500°C for 2 hours to prepare a catalyst precursor I;
[0120] (b) 1100 ml of catalyst precursor I was immersed in a mixed aqueous solution of chloropalladic acid and chloroauric acid, with a solid-liquid volume ratio of 1:1.2, wherein the palladium content in the solution was 2.75 g / L and the gold content was 0.625 g / L, and then dried at 80° C. for 8 hours to prepare catalyst precursor II;
[0121] (c) adding 100 ml of sodium silicate aqueous solution (27.5 g of Na2SiO3·9H2O is prepared into 100 ml of aqueous solution), mixing well and letting stand for 24 hours, and then drying at 80° C. for 8 hours to obtain catalyst precursor III;
[0122] (d) adding 60 g of 85 wt % hydrazine hydrate for reduction, standing for 4 hours, then washing with deionized water, and drying at 100° C. for 6 hours to obtain catalyst precursor IV;
[0123] (e) The catalyst precursor IV was impregnated with an aqueous solution of potassium acetate and dried at 80° C. for 2 h to obtain a finished catalyst, wherein the potassium acetate content in the catalyst was 30 g / L.
[0124] 2. Catalyst evaluation
[0125] The catalyst evaluation method was the same as in Example 1.
[0126] For the convenience of comparison, the experimental results are listed in Table 1.
[0127] Comparative Example 2
[0128] 1. Catalyst preparation
[0129] (a) Take 1100 ml of spherical silica carrier (diameter 5 mm, specific surface area 175 m 2 / g, pore volume is 0.8cm 3 / g) was immersed in a mixed aqueous solution of chloropalladic acid and chloroauric acid, calculated according to a solid-liquid volume ratio of 1:1.2, wherein the content of palladium in the solution used was 2.75 g / L and the content of gold was 0.625 g / L, and then dried at 80° C. for 8 hours to prepare a catalyst precursor I;
[0130] (b) adding 100 ml of sodium silicate aqueous solution (27.5 g of Na2SiO3·9H2O is prepared into 100 ml of aqueous solution), mixing well and letting stand for 24 hours, and then drying at 80°C for 8 hours to obtain catalyst precursor II;
[0131] (c) adding 60 g of 85 wt % hydrazine hydrate for reduction, standing for 4 hours, then washing with deionized water, and drying at 100° C. for 6 hours to obtain catalyst precursor III;
[0132] (d) Catalyst precursor III was impregnated with potassium acetate aqueous solution and dried at 80°C for 2 h to obtain a finished catalyst, wherein the potassium acetate content in the catalyst was 30 g / L.
[0133] 2. Catalyst evaluation
[0134] The catalyst evaluation method was the same as in Example 1.
[0135] For the convenience of comparison, the experimental results are listed in Table 1.
[0136] Table 1
[0137] Pd-N3 coverage on catalyst surface Catalyst space time yield, g / L·hr Catalyst selectivity, % Example 1 2.4% 448 94.5 Example 2 5.1% 449 94.7 Example 3 9.8% 443 94.4 Example 4 5.3% 452 95.4 Example 5 5.8% 458 95.9 Example 6 5.4% 455 95.8 Comparative Example 1 11.8% 383 93.0 Comparative Example 2 0 387 92.7
[0138] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A catalyst for preparing vinyl acetate, characterized in that: The coverage of the Pd-N3 sites on the surface of the catalyst is 0-10%.
2. The catalyst according to claim 1, wherein The coverage rate of Pd-N3 sites on the surface of the catalyst is between 2% and 10%.
3. The catalyst according to claim 1 or 2, wherein The catalyst includes a carrier and Pd, IB group metal and alkali metal acetate loaded on the carrier; Preferably, The IB group metal is Au and / or Cu, preferably Au; and / or The alkali metal element is selected from one or more of Li, Na, K, Rb, Cs and Fr, preferably one or more of Na and K; and / or The carrier is selected from one or more of silicon oxide and aluminum oxide; Preferably, the carrier is selected from spherical silica, preferably the diameter of the spherical silica is 2-8 mm and the specific surface area is 150-200 m 2 / g, pore volume is 0.6-1cm 3 / g.
4. The catalyst according to claim 3, wherein Calculated as an element, the Pd content is 1 to 12 g / L.
5. The catalyst according to claim 3 or 4, wherein Calculated as an element, the amount of Au is 0.1 to 10 g / L.
6. The catalyst according to any one of claims 3 to 5, wherein The content of alkali metal acetate is 10-100 g / L.
7. The catalyst according to any one of claims 3 to 6, wherein The alkali metal acetate is potassium acetate.
8. The method for preparing the catalyst according to any one of claims 1 to 7, characterized in that: The method includes: (a) impregnating a carrier source into a C3N4 dispersion and calcining to prepare a catalyst precursor I; (b) immersing the catalyst precursor I in a solution containing palladium and group IB metals, and drying to prepare a catalyst precursor II; (c) treating the catalyst precursor II with a solution of an alkaline compound and drying to obtain a catalyst precursor III; (d) reducing the noble metal ions of catalyst precursor III and drying to obtain catalyst precursor IV; (e) Impregnating the catalyst precursor IV with alkali metal acetate and drying.
9. The method according to claim 8, wherein: In step (a), The diameter of C3N4 in the C3N4 dispersion is 0.1 to 10 microns; and / or The content of C3N4 in the C3N4 dispersion is 5-20wt%; and / or The solvent in the dispersion is selected from one or more of deionized water; and / or Preferably, the dispersion contains an auxiliary agent, and the auxiliary agent is selected from one or more of acetic acid and ammonium acetate: more preferably, the auxiliary agent content is 0.1-10 mmol / L; and / or The solid-liquid volume ratio is 1:1 to 1.5; Drying is performed before calcination, and the preferred calcination conditions include: 300-500°C; and / or The operating conditions in step (b) include: The solid-liquid volume ratio is 1:1-1.
2. In the solution containing the Pd source and the IB group metal source, the content of Pd is 1-12 g / L, preferably 2-3 g / L, and the content of the IB group metal is 0.1-10 g / L, preferably 0.4-0.8 g / L. and / or The conditions in step (c) include: the concentration of the alkaline compound solution is 10-30% by weight, and the volume ratio of the alkaline compound solution to the carrier is 0.05-0.5, preferably 0.07-0.1; and / or In step (c), the alkaline compound is selected from one or more of sodium silicate and sodium hydroxide.
10. A method for preparing vinyl acetate, comprising: subjecting a raw material gas for synthesizing vinyl acetate to a gas-phase catalytic synthesis reaction in the presence of a catalyst, wherein: The catalyst comprises the catalyst according to any one of claims 1 to 7; Preferably, the raw gas for synthesizing vinyl acetate comprises oxygen, ethylene, nitrogen and acetic acid; Preferably, In terms of molar ratio, the molar ratio of oxygen, ethylene, nitrogen and acetic acid is 1:(5-7):(4-8):(1-2); and / or The conditions for the gas phase catalytic synthesis reaction include: The reaction pressure is 0.5-0.9 MPa, and / or The reaction temperature is 130-200°C, and / or The raw gas volume space velocity is 1600~3000hr -1 .
Citation Information
Patent Citations
Process for the preparation of catalysts for use in the production of vinyl acetate
CN1107831A
Palladium-gold catalyst for preparing vinyl acetate
CN1226188A
Method of catalyst preparation
GB1283737A
Process for the manufacture of vinyl acetate
CA754594A
Preparation method of Pd / C catalyst
CN103120936A